Síntese e caracterização de ferrita ni-zn pelo método dos precursores poliméricos calcinada por energia de microondas - Assis, Raimison Bezerra de (2013)
Magnetic ceramics have been widely investigated, especially with respect to intrinsic and extrinsic characteristics of these materials. Among the magnetic ceramic materials of technological interest, there are the ferrites. On the other hand, the thermal treatment of ceramic materials by microwave energy has offered various advantages such as: optimization of production processes, high heat control, low consumption of time and energy among others. In this work were synthesized powders of Ni-Zn ferrite with compositions Ni1- xZnxFe2O4 (0.25 ≤ x ≤ 0.75 mols) by the polymeric precursor route in two heat treatment conditions, conventional oven and microwave energy at 500, 650, 800 and 950°C and its structural, and morphological imaging. The materials were characterized by thermal analysis (TG/ DSC), X-ray diffraction (XRD), absorption spectroscopy in the infrared (FTIR), scanning electron microscopy (SEM), X-ray spectroscopy and energy dispersive (EDS) and vibrating sample magnetometry (VSM). The results of X-ray diffraction confirmed the formation of ferrite with spinel-type cubic structure. The extrinsic characteristics of the powders obtained by microwave calcination and influence significantly the magnetic behavior of ferrites, showing particles ferrimagnéticas characterized as soft magnetic materials (soft), is of great technological interest. The results obtained led the potential application of microwave energy for calcining powders of Ni-Zn ferrite